Reduced spontaneous platelet aggregation: a novel risk factor for adverse pregnancy outcome. (April 2016) - Burke, Naomi; Flood, Karen; Muellers, Sieglinde; Murray, Aoife; Dunne, Eimear; Cotter, Brian; Dempsey, Mark; Dicker, Patrick; Geary, Michael P.; Kenny, Dermot; Malone, Fergal D.
Abstract: Objective: Spontaneous platelet aggregation has not been adequately assessed as a potential risk factor for adverse outcomes in pregnancy. Therefore the objective of this study was to assess spontaneous platelet aggregation (SPA), measured via a novel functional assay, as a risk factor for hypertensive disease and intra-uterine growth restriction (IUGR). Study design: This was a prospective longitudinal study. Spontaneous platelet aggregation was assessed as a marker of platelet reactivity using a modification of light transmission aggregometry. Platelet reactivity was assessed in four groups: non-pregnant healthy female volunteers ( n = 30), longitudinally in normal uncomplicated pregnancy ( n = 50), hypertensive disorder ( n = 40) and IUGR ( n = 30). The mean percentage SPA was plotted and compared across all groups. Results: Spontaneous platelet aggregation was significantly reduced in the first trimester compared to the non-pregnant group ( p -value = 0.003). The mean aggregation for the hypertensive group was 1.9%, (95% CI −0.08 to 4.02) and for the IUGR group was 1.6%, (95% CI −0.6 to 3.72). Platelet aggregation in the hypertensive group was significantly reduced compared to the normal pregnant group ( p < 0.05). Spontaneous platelet aggregation was also reduced in the IUGR group compared to normal pregnancy ( p < 0.05). Conclusion: This study demonstrates that a reduction of spontaneous platelet aggregation may be a novel risk factor for adverse pregnancy outcomes such as pre-eclampsia and IUGR. The most clinically significant finding is that SPA is significantly lower in pregnancies complicated by hypertension and IUGR compared to those who had a normal pregnancy outcome. Further studies should be carried out to asses if spontaneous platelet aggregation may be a clinically useful tool for the prediction of pre-eclampsia and IUGR.